Preparation method and application of dual MOFs functional composite material for methane production by VOCs gas adsorption degradation

By constructing bimetallic MOFs materials, the problem of industrial VOCs gas removal is solved, efficient adsorption and photocatalytic degradation of toluene are achieved, and the methane generation rate and degradation efficiency are significantly improved.

CN115870009BActive Publication Date: 2025-02-21XIAN UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211632794.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-02-21
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove volatile organic compounds (VOCs) gases emitted from industrial production, especially toluene, which not only leads to environmental pollution, but also poses a threat to human health.

Method used

By constructing a bimetallic organic frame material (MOFs) for methane production by gas adsorption and degradation of VOCs, this material constructs a hierarchical porous structure by adjusting the molar ratio of chromium and zirconium, and combines the characteristics of NH2-UIO-66 and MIL-101 to achieve selection Adsorption and photocatalytic degradation.

Benefits of technology

Highly efficient adsorption and degradation of VOCs gases are achieved, which significantly improves the methane generation rate, and ensures degradation efficiency and safety due to the high specific surface area and chemical stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115870009B_ABST
    Figure CN115870009B_ABST
Patent Text Reader

Abstract

The present invention proposes a dual MOFs functional composite material for VOCs gas adsorption and degradation to produce methane. The dual MOFs heterogeneous structure can be used as a highly adjustable platform by adjusting the molar ratio of metal particles, and the pore structure can be adjusted according to the target gas to be adsorbed to achieve selective adsorption. Secondly, NH2-UIO-66 is a low-cost, non-toxic, and highly catalytically active adsorption and degradation material that can effectively ensure the degradation efficiency of VOCs gas molecules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of industrial VOCs gas adsorption and degradation, and specifically relates to a preparation method and application of a dual MOFs functional composite material for producing methane through VOCs gas adsorption and degradation. Background Art

[0002] Volatile organic compounds (VOCs) are the main types of waste gas emitted in industrial production, including many alkanes, alkenes, alcohols, aldehydes, ketones, esters, terpenes, carbonyl compounds and organic acids. This toxic VOC gas can cause serious environmental pollution and even endanger human health. Removing toxic gas pollutants from the air is essential for improving the air quality of indoor environments and maintaining human health. Toluene (the so-called phenylmethane and methylbenzene) is one of the main components of VOCs in the air. Acute contact with this compound can affect the central nervous system, causing headaches, loss of control, convulsions, coma and even death. Due to the inherent characteristics of toluene, including its high oxidation potential and highly stable structure, photocatalytic degradation is an effective way to save energy.

[0003] Metal organic frameworks (MOFs) are a new type of porous material, which is composed of metal ions or metal clusters interconnected with organic linkers such as carboxylates or phosphonates. They have large surface area, high porosity, chemical stability and controllable structure, and show great potential in drug delivery, catalysis, gas storage and selective adsorption. MIL-101 (Cr) is a porous material, mainly because it not only has a high specific surface area and mesoporosity, but also has a high concentration of open metal sites (~3.0mmol / g45-46), as well as high chemical stability, which can effectively capture VOCs gas molecules.

[0004] NH 2 -UIO-66 is a new type of MOF material with excellent hydrothermal and physicochemical stability. Its narrow band gap of 2.6-2.9 eV makes NH 2 -UIO-66 has excellent visible light excitation properties, which enables the photogenerated electrons and holes to be well utilized and separated. 2 -functional groups can further enhance its selective adsorption properties for target gases and can effectively photocatalyze the degradation of low-concentration toxic gases.

[0005] On this basis, the present invention constructs a dual MOFs functional composite material for VOCs gas adsorption and degradation to produce methane. By combining the unique structure and properties of chromium-based and zirconium-based MOF systems, a chromium-zirconium bimetallic MOFs heterostructure is prepared by in-situ loading. This heterostructure has hierarchical porous properties, and by adjusting the molar ratio of Zr / Cr in MOF, a hierarchical pore structure composed of micropores and mesopores can be systematically designed. NH 2 -UIO-66 has a large surface area and abundant active sites, which improves its photocatalytic performance, and the high porosity of MIL-101 allows VOCs gas molecules to form a large surface area on TiO 2 The surface is enriched in large quantities, further improving the degradation efficiency of VOCs gases. Summary of the invention

[0006] In view of the large amount of VOCs gas generated in the current coal chemical production process, a dual MOFs functional composite material for VOCs gas adsorption and degradation to produce methane was constructed. The dual MOFs heterogeneous structure can be used as a highly adjustable platform by adjusting the molar ratio of metal particles, and the pore structure can be adjusted according to the target gas to achieve selective adsorption. 2 -UIO-66 is a low-cost, non-toxic, and highly catalytically active adsorption and degradation material that can effectively ensure the degradation efficiency of VOCs gas molecules.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a dual MOFs functional composite material for producing methane by adsorption and degradation of VOCs gas, comprising the following steps:

[0009] S1. Synthesis of chromium-based metal-organic framework substrate materials

[0010] S1-1, adding chromium nitrate nonahydrate and phthalic acid into deionized water, and preparing a uniform mixed solution by ultrasonic dispersion;

[0011] S1-2, transferring the mixed solution prepared in S1-1 to a stainless steel reactor with a polytetrafluoroethylene liner to perform a hydrothermal reaction;

[0012] S1-3, after the hydrothermal autoclave in S1-2 is cooled to room temperature, it is first washed with deionized water using a centrifuge, and then washed with a methanol solution, and the green precipitate is transferred into a vacuum oven for vacuum drying to obtain a green powder: MIL-101;

[0013] S2. Preparation of a dual-MOFs functional composite material for VOCs gas adsorption and degradation to produce methane

[0014] S2-1, adding the MIL-101 powder obtained in S1-3 to the N,N-dimethylformamide solution, and dispersing by sealed ultrasonication to prepare a uniform mixed solution;

[0015] S2-2, weighing zirconium chloride, 2-aminoterephthalic acid and acetic acid, adding them to the mixed solution of S2-1, and preparing a uniform mixed solution by sealed ultrasonic dispersion;

[0016] S2-3, transferring the mixed solution prepared in S2-2 to a stainless steel reactor with a polytetrafluoroethylene liner to perform a hydrothermal reaction;

[0017] S2-4. After the hydrothermal autoclave in S2-2 is cooled to room temperature, the centrifuge is used to first wash it with N,N-dimethylformamide, and then with ethanol solution. The green precipitate is transferred to a vacuum oven for vacuum drying to obtain a yellow-green powder: MIL-101@NH 2 -UIO-66.

[0018] Preferably, in step S1:

[0019] In step S1-1, the mixing ratio of chromium nitrate nonahydrate and phthalic acid is 1:1 by mole, and the stirring time is not less than 30 minutes;

[0020] The hydrothermal reaction temperature in step S1-2 is 180° C., and the reaction time shall not be less than 15 hours;

[0021] In step S1-3, deionized methanol and deionized water are used for centrifugal washing in sequence, and the washing times are no less than 3 times.

[0022] Preferably, in step S2:

[0023] In step S2-1, the stirring time of MIL-101 and N,N-dimethylformamide solution is not less than 20 minutes;

[0024] The mixing ratio of zirconium chloride and 2-aminoterephthalic acid in step S2-2 is 1:1 by mole, and the stirring time is not less than 30 minutes;

[0025] In step S2-2, the mixing ratio of MIL-101 and zirconium chloride is at least one of the following three: molar ratio: 4:1, 2:1, 1:1;

[0026] In step S2-3, the hydrothermal reaction temperature is 120° C., and the reaction time is not less than 24 hours;

[0027] In step S2-4, N,N-dimethylformamide and ethanol are used for centrifugal washing in sequence, and the washing times are no less than 3 times, and the vacuum drying temperature is 70°C.

[0028] Application of dual MOFs functional composite material for methane production by VOCs gas adsorption and degradation obtained by the above preparation method.

[0029] The specific steps for the above purpose are as follows: The steps are as follows:

[0030] SA1, MIL-101@NH 2 -UIO-66 was placed in a double-layer photocatalytic reactor with a volume of 100 ml. The VOCs gas was connected to the input part of the reactor, and a flow meter was added in the gas path to control the flow rate. The output of the reactor was connected to a gas washing bottle to collect the waste gas.

[0031] SA2. In order to make the air in the reactor evenly distributed, the air was ventilated at a flow rate for 30 minutes with the light source turned off, and then the input and output ends were closed to form a closed space filled with VOCs gas;

[0032] SA3. Place the light source vertically on the upper part of the reactor, toward the center, and turn on the light source.

[0033] SA4. Take 200 ml of gas from the reactor gas inlet every 30 minutes and inject it into the gas chromatograph for quantitative measurement to explore the removal efficiency;

[0034] SA5. Add deionized water as a hydrogen source to the lower layer of the reactor to explore ways to cleanly reuse degradation products.

[0035] Preferably, in step SA1, 0.2 mg mL-1 of MIL-101@NH2-UIO-66 is placed in the reactor.

[0036] Preferably, in step SA2, the VOCs gas used is toluene gas, and the gas flow rate is 100 ml min -1 .

[0037] Preferably, in step SA3, the light source used is an ultraviolet (UV) lamp with a power of 8W, and the maximum emission and intensity of the lamp are 365nm and 1.52mW / cm 2 .

[0038] Preferably, in step SA5, the amount of deionized water added is equal to that of MIL-101@NH 2 -UIO-66 is 2 g / mL.

[0039] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0040] 1. The highly adjustable platform constructed by adjusting the molar ratio of the bimetallic molecules can adjust the pore structure to achieve selective adsorption of different gases.

[0041] 2. The dual MOFs functional composite material obtained in this application has a methane gas generation rate of 18.63342 μmol / g, and the dual MOFs functional composite material has a large specific surface area of ​​1859.5290 m 2 / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The X-ray diffraction patterns of Examples 1, 2 and 3 are as follows: Figure 1 As shown;

[0043] Figure 2 are scanning electron microscope images (SEM) of Examples 1, 2, and 3;

[0044] Figure 3 It is the N2 adsorption isotherm diagram (BET) of Examples 1, 2 and 3. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If no specific conditions are specified in the examples, the experiments are carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0046] Embodiment one:

[0047] The synthesis process of composite material M-1, the specific steps are as follows:

[0048] MIL-101 synthesis: Weigh 0.625 mM chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) and 0.625 mM terephthalic acid (C 8 H 6 O 4 ) was added to 10 mL of deionized water and ultrasonically dispersed for 20 minutes. The mixture was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated to 180°C for hydrothermal reaction for 15 hours. The mixture was cooled to room temperature, centrifuged and collected, and washed with deionized water and methanol for 3 times each, and dried under vacuum at 70°C.

[0049] Preparation of a dual MOFs functional composite material for VOCs gas adsorption and degradation to produce methane:

[0050] Weigh 0.09g of MIL-101 powder and add it to 50mL of N,N-dimethylformamide solution, seal and ultrasonic for 20 minutes to mix the solution evenly. Then weigh 0.074g of zirconium chloride, 0.072g of 2-aminoterephthalic acid and 5.5mL of acetic acid and add them to the above solution, continue to seal and ultrasonically disperse for 30 minutes to prepare a uniform mixed solution; then transfer it to a stainless steel reactor with a polytetrafluoroethylene liner and perform a hydrothermal reaction at 120°C for 24 hours. After the hydrothermal reactor is cooled to room temperature, it is washed three times with N,N-dimethylformamide and ethanol solution respectively through a centrifuge, and then the yellow-green precipitate is moved into a vacuum oven and vacuum dried at 70°C to finally obtain M-1.

[0051] Embodiment two:

[0052] The synthesis process of the composite material M-2, the specific steps are as follows:

[0053] MIL-101 synthesis: Weigh 0.625 mM chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) and 0.625 mM terephthalic acid (C 8 H 6 O 4 ) was added to 10 mL of deionized water and ultrasonically dispersed for 20 minutes. The mixture was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated to 180°C for hydrothermal reaction for 15 hours. The mixture was cooled to room temperature, centrifuged and collected, and washed with deionized water and methanol for 3 times each, and dried under vacuum at 70°C.

[0054] Preparation of a dual MOFs functional composite material for VOCs gas adsorption and degradation to produce methane:

[0055] Weigh 0.045g of MIL-101 powder and add it to 50mL of N,N-dimethylformamide solution, seal and ultrasonic for 20 minutes to mix the solution evenly. Then weigh 0.074g of zirconium chloride, 0.072g of 2-aminoterephthalic acid and 5.5mL of acetic acid and add them to the above solution, continue to seal and ultrasonically disperse for 30 minutes to prepare a uniform mixed solution; then transfer it to a stainless steel reactor with a polytetrafluoroethylene liner and perform a hydrothermal reaction at 120°C for 24 hours. After the hydrothermal reactor is cooled to room temperature, it is washed three times with N,N-dimethylformamide and ethanol solution respectively through a centrifuge, and then the yellow-green precipitate is moved into a vacuum oven and vacuum dried at 70°C to finally obtain M-2.

[0056] Embodiment three:

[0057] The synthesis process of the composite material M-3, the specific steps are as follows:

[0058] MIL-101 synthesis: Weigh 0.625 mM chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) and 0.625 mM terephthalic acid (C 8 H 6 O 4 ) was added to 10 mL of deionized water and ultrasonically dispersed for 20 minutes. The mixture was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated to 180°C for hydrothermal reaction for 15 hours. The mixture was cooled to room temperature, centrifuged and collected, and washed with deionized water and methanol for 3 times each, and dried under vacuum at 70°C.

[0059] Preparation of a dual MOFs functional composite material for VOCs gas adsorption and degradation to produce methane:

[0060] Weigh 0.18g of MIL-101 powder and add it to 50mL of N,N-dimethylformamide solution, seal and ultrasonic for 20 minutes to mix the solution evenly. Then weigh 0.074g of zirconium chloride, 0.072g of 2-aminoterephthalic acid and 5.5mL of acetic acid and add them to the above solution, continue to seal and ultrasonically disperse for 30 minutes to prepare a uniform mixed solution; then transfer it to a stainless steel reactor with a polytetrafluoroethylene liner and perform a hydrothermal reaction at 120°C for 24 hours. After the hydrothermal reactor is cooled to room temperature, it is washed three times with N,N-dimethylformamide and ethanol solution respectively through a centrifuge, and then the yellow-green precipitate is moved into a vacuum oven and vacuum dried at 70°C to finally obtain M-3.

[0061] Comparative Example 1:

[0062] MIL-101 synthesis: Weigh 0.625 mM chromium nitrate nonahydrate (Cr(NO 3 ) 3 9H 2 O) and 0.625 mM terephthalic acid (C 8 H 6 O 4 ) was added to 10 mL of deionized water and ultrasonically dispersed for 20 minutes. The mixture was then transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated to 180°C for hydrothermal reaction for 15 hours. The mixture was cooled to room temperature, centrifuged and collected, and washed with deionized water and methanol for 3 times each, and dried under vacuum at 70°C.

[0063] Comparative Example 2:

[0064] NH 2-UIO-66 synthesis: Weigh 0.074g zirconium chloride, 0.072g 2-aminoterephthalic acid and 5.5mL acetic acid and add them to 50mL N,N-dimethylformamide solution, seal and ultrasonically disperse for 30 minutes to prepare a uniform mixed solution; then transfer to a stainless steel reactor with a polytetrafluoroethylene liner and perform a hydrothermal reaction at 120°C for 24 hours. After the hydrothermal reactor is cooled to room temperature, it is washed three times with N,N-dimethylformamide and ethanol solution respectively through a centrifuge, and then the light yellow precipitate is moved into a vacuum oven and vacuum dried at 70°C to finally obtain a light yellow powder: NH 2 -UIO-66.

[0065] The specific surface areas of Examples 1, 2, 3 and Comparative Examples 1 and 2 are shown in Table 1;

[0066]

[0067] Figure 1 The X-ray diffraction patterns of Example 3 and Comparative Examples 1 and 2, 2θ = 5°-30° belong to typical MIL-101 (Cr) and NH 2 -UiO-66(Zr), indicating that comparative examples 1 and 2 were successfully synthesized, and NH 2 The peak of -UiO-66(Zr) also appears in MIL-101(Cr), indicating that NH 2 -UiO-66(Zr) was successfully introduced into MIL-101(Cr). Compared with pure MIL-101(Cr), the introduced NH 2 -UiO-66(Zr) still has many high and sharp peaks, which indicates that the crystallization properties have not changed after the two phases are composited, and still maintain excellent grain size and high crystallinity.

[0068] Figure 2 The SEM images of Example 3 and Comparative Examples 1 and 2 are shown in FIG. Figure 2 Figures a and b show pure MIL-101(Cr) and NH 2 -UiO-66 morphology, the average grain size of MIL-101(Cr) is about 120nm, NH 2 The average grain size of -UiO-66 is about 140nm. 2 -After UiO-66 was introduced into MIL-101(Cr), NH 2 -UiO-66 grain size is significantly reduced, which may be due to the presence of MIL-101(Cr) inhibiting the NH 2 -UiO-66 grain growth results. With the different amounts of MIL-101(Cr) introduced, NH 2 -UiO-66 grain size also changes with the change of NH2 -The average grain size of UiO-66 is about 65nm ( Figure 2 c) NH in M-2 2 -The average grain size of UiO-66 is about 35nm ( Figure 2 d), NH in M-3 2 -The average grain size of UiO-66 is about 40nm ( Figure 2 e), while the grain size of MIL-101(Cr) did not change significantly. In the photocatalytic reaction, a smaller particle size will shorten the diffusion distance of photogenerated charge carriers in MOFs, enrich the surface reaction sites, and be more conducive to the photocatalytic reaction.

[0069] Figure 3 The nitrogen adsorption curves of Examples 1, 2, and 3 and Comparative Examples 1 and 2 show that all samples show type IV curves, indicating a mesoporous structure. 2 -The specific surface areas of UiO-66, M-1, M-2 and M-3 are 1733.5870 m 2 / g, 571.9770m 2 / g, 1859.5290m 2 / g, 1208.1580m 2 / g, 1,101.88m 2 / g. In addition, MIL-101(Cr), NH 2 The average pore size of -UiO-66 is 2.9nm and 7.2nm. The larger pore size is greatly reduced after the two-phase composite. The average pore size of M-1, M-2, and M-3 is 4.2nm, 4.3nm, and 3.4nm. The specific surface area of ​​MIL-101(Cr) is larger than that of M-2 and M-3, which may be because the pore surface is covered by NH 2 -UiO-66 is occupied, and NH 2 The pore size of -UiO-66 is larger than that of the two-phase composite, which may be due to the NH 2 -UiO-66 is blocked by MIL-101(Cr), and this result can also prove that NH 2 -UiO-66 was successfully introduced into MIL-101(Cr).

[0070] In the case of adding deionized water, the photocatalytic reduction of toluene to produce CH during the 8 h illumination period in Examples 1, 2, and 3 and Comparative Examples 1 and 2 was carried out. 4 Performance test. In the presence of a single MIL-101 CH 4 The growth rate of is slow, and after the two are combined, CH 4 The generation efficiency is greatly improved, pure MIL-101(Cr) and NH 2- Average CH produced per hour by UiO-66 4 The amount of -1 g -1 and 3.24 μmolh -1 g -1 , M-1 produces an average of CH 4 The amount is 18.63 μmolh -1 g -1 M-1 generates CH 4 The amounts are pure MIL-101(Cr) and NH 2 -UiO-66 is about 3 times and 5 times. The above phenomenon indicates that after the two are combined, thanks to the synergistic effect between the two, MIL-101(Cr) and NH 2 The transport of electrons between the interfaces of -UiO-66 is accelerated, the recombination of electrons and holes between the interfaces is suppressed, and the separation efficiency of excited electron-hole pairs is improved.

Claims

1. An application of a dual MOFs functional composite material for methane production by VOCs gas adsorption and degradation, characterized in that: The method for preparing the dual MOFs functional composite material for producing methane by adsorption and degradation of VOCs gas comprises the following steps: S1. Synthesis of chromium-based metal-organic framework substrate materials S1-1, adding chromium nitrate nonahydrate and phthalic acid into deionized water, and preparing a uniform mixed solution by ultrasonic dispersion; the mixing ratio of chromium nitrate nonahydrate and phthalic acid is 1:1 by mole, and the stirring time is not less than 30 minutes; S1-2, transfer the mixed solution prepared in S1-1 to a stainless steel reactor lined with polytetrafluoroethylene for hydrothermal reaction; the hydrothermal reaction temperature is 180°C, and the reaction time shall not be less than 15 hours; S1-3, after the hydrothermal autoclave in S1-2 is cooled to room temperature, the autoclave is first washed with deionized water using a centrifuge, and then washed with a methanol solution, and the number of washing times is not less than 3 times; the green precipitate is transferred to a vacuum oven for vacuum drying to obtain a green powder: MIL-101; S2. Preparation of a dual-MOFs functional composite material for VOCs gas adsorption and degradation to produce methane S2-1, adding the MIL-101 powder obtained in S1-3 to the N,N-dimethylformamide solution, and preparing a uniform mixed solution by sealed ultrasonic dispersion; the MIL-101 and N,N-dimethylformamide solution are stirred for not less than 20 minutes; S2-2, weigh zirconium chloride, 2-aminoterephthalic acid and acetic acid, add them to the mixed solution of S2-1, and prepare a uniform mixed solution by sealed ultrasonic dispersion; the mixing ratio of zirconium chloride and 2-aminoterephthalic acid is 1:1, and the stirring time is not less than 30 minutes; the mixing ratio of MIL-101 and zirconium chloride is at least one of the following three: molar ratio: 4:1, 2:1, 1:1; S2-3, transfer the mixed solution prepared in S2-2 to a stainless steel reactor lined with polytetrafluoroethylene for hydrothermal reaction; the hydrothermal reaction temperature is 120°C, and the reaction time shall not be less than 24 hours; S2-4. After the hydrothermal autoclave in S2-2 is cooled to room temperature, use a centrifuge to wash it with N,N-dimethylformamide and ethanol in succession, and the washing times shall be no less than 3 times. Move the green precipitate into a vacuum oven for vacuum drying at a vacuum drying temperature of 70°C to obtain a yellow-green powder: MIL-101@NH2-UIO-66.

2. The use according to claim 1, characterized in that: The specific steps are as follows: SA1. Place MIL-101@NH2-UIO-66 into a double-layer photocatalytic reactor with a volume of 100 ml, connect VOCs gas to the input part of the reactor, and add a flow meter in the gas path to control the flow rate; connect the output of the reactor to a gas washing bottle to collect waste gas; SA2. In order to make the air in the reactor evenly distributed, the air was ventilated at a flow rate for 30 minutes with the light source turned off, and then the input and output ends were closed to form a closed space filled with VOCs gas; SA3, place the light source vertically on the upper part of the reactor, toward the center, and turn on the light source; SA4. Take 200 ml of gas from the reactor gas inlet every 30 minutes and inject it into the gas chromatograph for quantitative measurement to explore the removal efficiency; SA5. Add deionized water as a hydrogen source to the lower layer of the reactor to explore ways to cleanly reuse degradation products.

3. The use according to claim 2, characterized in that: In step SA1, 0.2 mg mL -1 MIL-101@NH2-UIO-66.

4. The use according to claim 2, characterized in that: In step SA2, the VOCs gas used is toluene gas, and the gas flow rate is 100 ml min -1 .

5. The use according to claim 2, characterized in that: In step SA3, the light source used is an ultraviolet (UV) lamp with a power of 8W, and the maximum emission and intensity of the lamp are 365nm and 1.52mW / cm 2 .

6. The use according to claim 2, characterized in that: In step SA5, the amount of deionized water added is 2 g / mL in relation to MIL-101@NH2-UIO-66.